2015
DOI: 10.1007/s12032-015-0600-4
|View full text |Cite
|
Sign up to set email alerts
|

Tight junction protein claudin-6 inhibits growth and induces the apoptosis of cervical carcinoma cells in vitro and in vivo

Abstract: Claudin-6, a member of claudin family integral membrane proteins, has recently been reported to be a tumor suppressor for breast cancer. However, whether it plays a role in other types of cancer remains unclear. In the present study, we showed that the expression of claudin-6 is down-regulated in cervical carcinoma tissues as revealed by immunohistochemistry. Through over-expressing claudin-6 in HeLa and C33A cervical carcinoma cells, we found that claudin-6 is localized at plasma membrane and it increases tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 35 publications
1
28
0
2
Order By: Relevance
“…Stress induced apoptosis worked through activation of the ASK1-p38 MAPK pathway (35)(36)(37). Several studied have shown that CLDNs induce apoptosis of cancer cells such as cervical carcinoma and breast cancer cells (17,(38)(39)(40). Our data showed that CLDN6 significantly inhibited MCF-7 cell apoptosis with TRX1 treatment.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Stress induced apoptosis worked through activation of the ASK1-p38 MAPK pathway (35)(36)(37). Several studied have shown that CLDNs induce apoptosis of cancer cells such as cervical carcinoma and breast cancer cells (17,(38)(39)(40). Our data showed that CLDN6 significantly inhibited MCF-7 cell apoptosis with TRX1 treatment.…”
Section: Discussionsupporting
confidence: 50%
“…Accumulating evidence suggests that CLDNs induce tumor apoptosis through activating MAPK signal pathway, such as CLDN6 induces tumor apoptosis through activating the ERK1/2 signaling pathway (17), and CLDN7 promotes apoptosis through the activation of p38 protein kinase in MKN28 gastric epithelial cells (18). The present study dissects the molecular mechanisms by which CLDN6 induced apoptosis in MCF-7 breast cancer cells.…”
Section: Introductionmentioning
confidence: 72%
“…Zhu et al noticed that the expression of claudin-5 and claudin-9 is downregulated in cervical carcinoma tissues compared with adjacent non-neoplastic tissues, while claudin-8 is elevated [74]. In contrast to claudin-1, claudin-6 is downregulated in cervical carcinoma, and expression of claudin-6 leads to decreased cell proliferation, colony formation in vitro, and tumor growth in vivo [116]. Based on this observation, it was suggested that this protein may be a tumor suppressor for cervical cancer.…”
Section: Claudins In Cervical Cancermentioning
confidence: 99%
“…A cell immunofluorescence assay was conducted as previously described. 24 In brief, after washing three times with PBS and fixed with 4% paraformaldehyde for 10 min at RT, the cells were permeabilized with 0.…”
Section: Immunofluorescence Methodsmentioning
confidence: 99%
“…The 4-μm thick sections were deparaffinized in xylene, rehydrated through a graded ethanol, series and coated in 3% hydrogen peroxide for 10 min at room temperature (RT) in order to block endogenous peroxidase activity, according to the protocol outlined in a previous study. 24 The sections were then stained with an anti-CLDN12 at a 1:350 dilution (cat. no.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%